The socioeconomic characteristics of ideal local candidates as preffered by voters in barangay Caitib, Miagao, Iloilo. - Occena, Maria Fiorella A.
This study was conducted to find out the socioeconomic characteristics of ideal local candidates as preferred by voters in rural area. Specifically, it aimed (1) to find out the preferred characteristics of local candidates as to their age, sex, civil status, educational attainment, religion, economic status, candidates' experience in politics, period of residency in the municipality, and political backgrounds of their families; (2) to distinguish and analyze the reasons for their preferences; (3) to find out if a voter's own characteristics (sex and voting experience) have any bearing on his /her preferences; (4) to characterize an ideal candidate based on the voters' preference; and (5) to compare the current municipal government officials and the ideal socioeconomic characteristics of candidates as identified in the previous study., the respondents composed of 16% of the total registered voters of the selected barangay in May 2001 elections. The data were gathered through personal interview with the respondents who were identified in random using the "lottery technique" (Ardales, 1992). The study revealed that the difference as to the preferences of both male and female respondents is considerable. A majority of all the respondents preferred the same socioeconomic characteristics of their ideal local candidates except with the political background of the candidates' families. The female respondents preferred candidates who were the first ones in their families to run for public office, majority of the male respondents preferred candidates who came from a family of politicians. The study revealed that respondents with low voting experience preferred the same socioeconomic characteristics of ideal local candidates except with the political background of the candidates' families. The majority of the respondents with low voting experience preferred the same highly socioeconomic characteristics as that of the respondents with medium voting experience except with economic status and political background of candidates. The latter prefer candidates who belong to the upper class and candidates who came from a family of politicians. The majority of the respondents with high voting experience preferred each of the highly preferred characteristics as that of the respondents with medium voting experience except of the economic status of the candidates. The respondents with high voting experience preferred candidates who belong to the middle class. The study concluded that the local ideal candidates preferred by voter-respondents considering their sex and voting experience in Brgy. Caitib, Miagao are aging from 31-50 years old, males, married, college graduates, Roman Catholics, belong to the municipality since birth/childhood, and who came from the family of politicians.